Ultrasound analysis of different forms of hemolytic uremic syndrome in children - Rink, Lydia; Finkelberg, Ilja; Kreuzer, Martin; Schipper, Lukas; Pape, Lars; Cetiner, Metin (Frontiers in Pediatrics, 2024)
Background: Hemolytic uremic syndrome (HUS) is the most common cause of acute kidney injury (AKI) in children caused mainly by Shiga toxin-producing enterohemorrhagic Escherichia coli (EHEC; STEC-HUS) and more rarely caused by uncontrolled complement activation (cHUS). Renal replacement therapy is required frequently; kidney function recovers in the majority. Ultrasound (US) represents the preferred imaging modality for the evaluation of any renal failure. Aim of this study is the evaluation of US diagnostics in both HUS types at disease onset and in the course.Materials and Methods: Clinical, laboratory and US data from digital patient records of children admitted as inpatients with a diagnosis of HUS were recruited for a monocentric, retrospective analysis. STEC-HUS and cHUS were diagnosed when in addition to the laboratory constellation, EHEC infection respectively complement system activation was verified. US examinations were performed by pediatricians with certified pediatric US experience.Results: Thirty children with STEC-HUS (13/25 male; median 2.9 years; most prevalent EHEC serotype O157) and cHUS (2/5 male; median 5.4 years, 3/5 with proven pathogenic variation) were included. Renal replacement therapy shares were comparable in STEC-and cHUS patients (64% vs. 60%). Resistance Index (RI) was elevated at disease onset with in patients with STEC-HUS and cHUS (0.88 ± 0.10 vs. 0.77 ± 0.04, p=0.13) and similar in the STEC-HUS subcohorts regarding dialysis requirement (yes: 0.86 ± 0.1; no: 0.88 ± 0.1; p = 0.74). Total kidney size at disease onset displayed positive correlation with dialysis duration (R=0.53, p=0.02) and was elevated in both HUS types (177% ± 56 and 167% ± 53), significantly higher in the STEC-HUS subcohort with dialysis requirement (200.7% vs. 145%, p < .029) and a regressor kidney size threshold value of 141% in the ROC analysis. A classification model using both US parameters sequentially might be of clinical use for predicting dialysis need in STEC-HUS. US parameters normalized over time.US parameters RI and total kidney size are valuable for the assessment of HUS at disease onset and during therapy, and may be helpful in assessment for dialysis requirement in STEC-HUS.